Applying the Growth Diagnostics Approach to Burundi - Kipuka Kabongi, Decky (Université d'Ottawa | University of Ottawa, 2012)
This research paper performs the growth diagnostics approach following the decision tree developed by Hausmann, Rodrik and Velasco (2005) in order to find the most binding constraints to economic growth in developing countries. The scope of the paper is limited to the Republic of Burundi, one of the poorest countries in the world that is located in the central African region and which is facing a slew of development challenges. The study finds that there exist many overlapping and complex factors that qualify as binding constraints to economic growth in Burundi. These constraints encompass the lack of access to finance, the absence of the rule of law, rampant corruption, a poor regulatory framework and macroeconomic governance, as well as the lack of physical infrastructures (most importantly roads and electricity) to support economic activities. Given this complexity of constraints and Burundi’s post-conflicts status, the study finds that the business environment is the major bottleneck to economic growth that the government has to first tackle in the short-term and expand the country’s private sector, a key engine for growth. The study acknowledges that other factors in the decision tree enumerated above are all constraining growth in Burundi and that releasing them will have positive impact on the economy and citizens’ wellbeing. However, reforming the regulatory framework appears to be a strategic policy agenda as the government cannot tackle all the problems together, due presumably to the lack of sufficient governance capacities and resources. The research paper’s methods of analysis are twofold: first, the paper analyses quantitative data on economic and development indicators obtained from secondary sources, such as reports on Burundi from the World Bank, the International Monetary Fund, the United Nations, the Organization for Economic Co-operation and Development (OECD), the African Development Bank and various reports produced by the government of Burundi. Second, the paper uses the literature review comprising academic publications as well as secondary sources. The structure of the paper is as follows. Chapter 1 presents the study’s analytical framework by succinctly examining how Burundi’s politics have evolved over time and their implications on the economy. Chapter 2 explains the growth diagnostics methodology as elaborated by its authors (Hausmann et al.). Chapter 3 performs the growth diagnostics approach with the aim of finding the most binding constraints to growth in Burundi.